A Note on Four Early York Account Rolls in the Bodleian Library, Oxford. (7th December 2022) - Beadle, Richard
Abstract : Four little-known account rolls now preserved (in part or as a whole) in the Bodleian Library, Oxford, two dating from the mid-fifteenth century and two from the mid-sixteenth, originally formed part of the civic archives at York. They consist of sets of Chamberlains' and Bridgemasters' accounts dated 1446–47, and of similar sets pertaining to the same bodies, the Chamberlains' (a fragment only) datable to 1533–34, and the Bridgemasters' dated 1541–42. All four formed part of the long series of fifteenth- and sixteenth-century rolls still among the early muniments of the city of York, but were unknown to R.B. Dobson and P.M. Stell, who in recent times edited, respectively, the Chamberlains' and Bridgemasters' rolls down to 1500. They were also overlooked by A.F. Johnston and M. Rogerson, who made numerous extracts relating to drama and cognate activities from the rolls in York for the volume devoted to the city in the series Records of Early English Drama . The article describes in brief the content of and physical condition of the Bodleian rolls, identifying two of the scribes involved in their compilation, and extracts from the Chamberlains' accounts for 1533–34, one entry relating to the Corpus Christi play and two to the city waits.